Effectiveness of the Treatment of Physiotherapy in the Congenital Muscular Torticollis: A Systematic Review - Manuel Rodríguez-Huguet; Daniel Rodríguez-Almagro; Miguel Ángel Rosety-Rodríguez; Maria Jesus Vinolo-Gil; Carmen Ayala-Martínez; Jorge Góngora-Rodríguez (MDPI AG, 2023)
A single congenital muscular torticollis (CMT) is a postural musculoskeletal deformity and is characterized by the shortening or stiffness of the sternocleidomastoid muscle. The reported incidence of CMT ranges from 0.2% to 2%. The objective is to evaluate the effect of physical therapy programs on CMT. For the search, PubMed, Scopus, Web of Science, PEDro and Cochrane databases were used. Randomized controlled trials published between 2018 and 2023 have been included. This study follows the PRISMA 2020 statement and has been registered in the PROSPERO database. Finally, six studies were included. The cervical range of motion (ROM) in rotation was the most analyzed variable, followed by the ultrasound evaluation; one of the studies included the analysis of children's motor development with the Alberta scale. All research found benefits associated with soft tissue mobilization, passive stretching techniques and manual therapy of the cervical spine. In conclusion, it is possible to recommend manual therapy and passive stretching techniques for the treatment of CMT, with significant results on the cervical ROM.